Hierarchical Beam Alignment in Single-User MIMO Single-Carrier Frequency Division Multiple Access Terahertz Communication Systems - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Gerstacker, Wolfgang (2021 IEEE International Conference on Communications Workshops, ICC Workshops 2021 - Proceedings, 2021)
Single-carrier frequency division multiple access (SC-FDMA) is a promising technique for high data rate Terahertz (THz) communications in future beyond 5G systems. Beam alignment (BA) is considered as a mandatory solution to establish a reliable communication link in SC-FDMA THz communication. However, existing BA methods introduce a large latency in searching for the optimal beam. In this paper, we propose a multi-armed bandit algorithm referred to as hierarchical beam alignment (HBA) for single-user SC-FDMA THz systems to reduce the beam alignment latency. HBA utilizes a hierarchical structure in the adopted codebook and the prior knowledge regarding the frequency-selective fading of the channel to speed up the BA process. Both theoretical analysis and simulation results illustrate that HBA converges to the optimal beam with high probability. The latency introduced by HBA is significantly lower compared to an exhaustive search method.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Beam alignment; indoor Terahertz communication; SC-FDMA

Hierarchical beam alignment in SU-MIMO terahertz communications - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Gerstacker, Wolfgang (ITU Journal: ICT Discoveries, 2021)
Single-Carrier Frequency Division Multiple Access (SC-FDMA) is a promising technique for high data rate indoor Terahertz (THz) communications in future beyond 5G systems. In an indoor propagation scenario, the Line-Of-Sight (LOS) component may be blocked by the obstacles. Thus, efficient THz SC-FDMA communications require a fast and reliable Beam Alignment (BA) method for both LOS and Non-Line-Of-Sight (NLOS) scenarios. In this paper, we first adopt the hierarchical discrete Fourier transform codebook for LOS BA, and introduce the hierarchical k-means codebook for NLOS BA to improve the beamforming gain. Simulation results illustrate that the hierarchical DFT codebook and the hierarchical k-means codebook can achieve the beamforming gain close to that of the maximum ratio transmission in LOS and NLOS cases, respectively. Based on these two codebooks, we propose a Multi-Armed Bandit (MAB) algorithm named Hierarchical Beam Alignment (HBA) for single-user SC-FDMA THz systems to reduce the BA latency. HBA utilizes a hierarchical structure in the adopted codebook and prior knowledge regarding the noise power to speed up the BA process. Both theoretical analysis and simulation results indicate that the proposed BA method converges to the optimal beam with high probability for both the hierarchical DFT codebook and the hierarchical k-means codebook in the LOS and NLOS scenarios, respectively. The latency introduced by HBA is significantly lower when compared to an exhaustive search method and other MAB-based methods.
Keywords: Beam alignment; codebook design; SC-FDMA; SU-MIMO; terahertz communications

ML Detection without CSI for Constant-Weight Codes in THz Communications with Strong Phase Noise - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Schober, Robert; Gerstacker, Wolfgang (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
To meet the ever-increasing requirements of high-rate data transmission, the significant amount of spectrum available in the TeraHertz (THz) band is considered for future wireless communications. However, the performance of THz communications is limited by strong phase noise (PN) introduced by oscillators and the complexity added by channel state information (CSI) acquisition. To overcome such impediments, we propose a new transmission concept based on constant-weight (CW) codes which enable low-complexity maximum-likelihood (ML) sequence detection at the receiver side in the presence of strong PN without requiring statistical or instantaneous CSI knowledge. In addition, the error rate of the ML receiver for the proposed CW codes is analyzed. Simulation results verify the analytical derivations and illustrate that the proposed transmission scheme outperforms transmission with on-off keying modulation and coherent detection.
CRIS-Team Scopus Importer:2023-03-07